Women and the historical enterprise in America : gender, race, and the politics of memory, 1880-1945 - Des Jardins, Julie (Gender & American culture., 2003)
"In Women and the Historical Enterprise in America, Julie Des Jardins explores American women's participation in the practice of history from the late nineteenth century through the end of World War II. During this transitional period, the study of history became professionalized as an increasingly masculine field of scientific inquiry, no longer considered a feminine realm of knowledge devoted to nostalgia for a patriotic past. Des Jardins reveals how women nevertheless transformed the historical profession and the construction of historical memory during these years in their roles as writers, preservationists, educators, government workers, archivists, and social activists." "Des Jardins explores the work of a wide variety of women historians, both professional and amateur, popular and scholarly, conservative and radical, white and nonwhite. Although their ability to earn professional credentials and to gain research access to official documents was limited by their gender (and often by their race), these historians addressed important new questions and represented social groups traditionally omitted from the historical record, such as workers, African Americans, Native Americans, and religious minorities. Assessing the historical contributions of Mary Beard, Zora Neale Hurston, Angie Debo, Mari Sandoz, Lucy Salmon, Mary McLeod Bethune, Dorothy Porter, Nellie Neilson, and many others, Des Jardins argues that women working within the broadest confines of the historical enterprise collectively brought the new perpectives of social and cultural history to the study of a multifaceted American past. In the process, they not only developed the field of women's history but also influenced the creation of our national memory in the twentieth century." "According to Des Jardins, women produced, preserved, and reinterpreted history for many different reasons, but they were united in their desire to broaden the field of inquiry. Taken together, their work reveals a growing activist impulse and historical consciousness and constitutes a historiographical legacy that remains relevant today."--Jacket